Asma Cake House Ordering Web-Based System - Muhammad Aliff Aiman, M. Tajuddin (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Online food ordering has seen a sharp increase in popularity in recent years, and many business owners now rely heavily on this new channel. It is widely acknowledged that launching a new small business and competing with established entrepreneurs in today's market is an extremely difficult task. Customers today are increasingly drawn to online shopping not only for its convenience but also for the easy access to information about products it provides. By using this platform, they can reach more people through internet thus making the business able to grow more and easily accessible for consumers compared to traditional methods. The Asma Cake House ordering web-based system is a platform that allows customers to order cakes online from Asma Cake House. The system allows customers to browse and select cakes from a catalogue, customize their orders, and pay for their orders. For the business side, the system provides an efficient inventory management system that helps Asma Cake House keep track of their stock and manage their orders in a more organized way. Overall, the Asma Cake House ordering web-based system provides a convenient and efficient way for customers to order cakes online, and it also helps Asma Cake House to manage their orders and inventory more effectively.